Varicella Zoster Virus Induces Nuclear Translocation of the Neurokinin-1 Receptor, Promoting Lamellipodia Formation and Viral Spread in Spinal Astrocytes. (19th May 2018) - Bubak, Andrew N; Como, Christina N; Blackmon, Anna M; Frietze, Seth; Mescher, Teresa; Jones, Dallas; Cohrs, Randall J; Paucek, Petr; Baird, Nicholas L; Nagel, Maria A
Abstract : Varicella zoster virus induces aberrant nuclear localization of the neurokinin-1 receptor in primary human spinal cord astrocytes, resulting in lamellipodia formation and viral spread that is blocked by the neurokinin-1 receptor antagonists aprepitant and rolapitant. Abstract: Background: Varicella zoster virus (VZV) can present as a myelopathy with spinal astrocyte infection. Recent studies support a role for the neurokinin-1 receptor (NK-1R) in virus infections, as well as for cytoskeletal alterations that may promote viral spread. Thus, we examined the role of NK-1R in VZV-infected primary human spinal astrocytes (HA-sps) to shed light on the pathogenesis of VZV myelopathy. Methods: Mock- and VZV-infected HA-sps were examined for substance P (subP) production, NK-1R localization, morphological changes, and viral spread in the presence or absence of the NK-1R antagonists aprepitant and rolapitant. Results: VZV infection of HA-sps induced nuclear localization of full-length and truncated NK-1R in the absence of the endogenous ligand, subP, and was associated with extensive lamellipodia formation and viral spread that was inhibited by NK-1R antagonists. Conclusions: We have identified a novel, subP-independent, proviral function of nuclear NK-1R associated with lamellipodia formation and viral spread that is distinct from subP-induced NK-1R cell membrane/cytoplasmic localization without lamellipodia formation. These results suggest that binding of a putative viral ligand to NK-1R produces a dramatically different NK-1R downstream effect than binding of subP. Finally, the NK-1R antagonists aprepitant and rolapitant provide promising alternatives to nucleoside analogs in treating VZV infections, including myelopathy.